Disruption of GM2/GD2 synthase gene resulted in overt expression of 9-O-acetyl GD3 irrespective of Tis211 - Furukawa, Keiko (Blackwell Publishing Ltd, 2008)
GM2/GD2 synthase gene knockout mice lack all complex gangliosides, which are abundantly expressed in the nervous systems of vertebrates. In turn, they have increased precursor structures GM3 and GD3, probably replacing the roles of the depleted complex gangliosides. In this study, we found that 9-O-acetyl GD3 is also highly expressed as one of the major glycosphingolipids accumulating in the nervous tissues of the mutant mice. The identity of the novel component was confirmed by neuraminidase treatment, thin layer chromatography-immunostaining, two-dimensional thin layer chromatography with base treatment, and mass spectrometry. All candidate factors reported to be possible inducer of 9-O- acetylation, such as bitamine D binding protein, acetyl CoA transporter, or O-acetyl ganglioside synthase were not up-regulated. Tis21 which had been reported to be a 9-O-acetylation inducer was partially down-regulated in the null mutants, suggesting that Tis21 is not involved in the induction of 9-O-acetyl-GD3 and that accumulated high amount of GD3 might be the main factor for the dramatic increase of 9-O-acetyl GD3. The ability to acetylate exogenously added GD3 in the normal mouse astrocytes was examined, showing that the wild-type brain might be able to synthesize very low levels of 9-O-acetyl GD3. Increased 9-O-acetyl GD3, in addition to GM3 and GD3, may play an important role in the compensation for deleted complex gangliosides in the mutant mice. J. Neurochem. (2008) 105, 1057–1066.